2022
DOI: 10.1016/j.cegh.2021.100951
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of hypertension complications among hypertensive patients at University of Gondar Comprehensive Specialized Referral Hospital

Abstract: Background: Cardiovascular diseases (CVDs) were non-communicable diseases that remain the leading cause of disability and death in the world. Therefore, this study aimed to assess the prevalence and associated factors of hypertension complications among hypertensive patients at University of Gondar comprehensive specialized referral hospital. Method: A cross-sectional study was conducted to assess the prevalence and associated factors of hypertension complications, from 1st June 2020 to 30th August 2020. Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…These results are consistent with those of previous clinical studies. A long-term phase 3 study with a multicenter, open-label design reported that CS-3150 2.5 mg/day or 5 mg/day for 12 or 28 weeks significantly decreased sitting SBP and DBP in patients with Primary hypertension [ 26 ]. A post-hoc analysis also demonstrated that CS-3150 improved night-time BP and N-terminal pro-B-type natriuretic peptide, which is a cardiovascular risk marker, based on different nocturnal BP dipping patterns (dippers, extreme dippers, non-dippers, and risers) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with those of previous clinical studies. A long-term phase 3 study with a multicenter, open-label design reported that CS-3150 2.5 mg/day or 5 mg/day for 12 or 28 weeks significantly decreased sitting SBP and DBP in patients with Primary hypertension [ 26 ]. A post-hoc analysis also demonstrated that CS-3150 improved night-time BP and N-terminal pro-B-type natriuretic peptide, which is a cardiovascular risk marker, based on different nocturnal BP dipping patterns (dippers, extreme dippers, non-dippers, and risers) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by increased force exerted by circulating blood through the walls of the major blood vessels in the body [ 1 ]. Although it often has no symptoms, the consequences are devastating that can lead to heart disease, stroke, vision loss, kidney failure and other serious complications [ 2 , 3 ]. The global burden of diseases report on mortality due to non-communicable diseases indicated that hypertension is the major cause of premature death.…”
Section: Introductionmentioning
confidence: 99%
“…The incidents of CVD are caused mainly by a patient's failure to comply with hypertension medication and uncontrolled high blood pressure (1). Globally, 17 million deaths are caused by cardiovascular disease, 9.4 million of which are caused by complications due to hypertension (2). Additionally, 2 million cases of hemorrhagic stroke, 1.5 million cases of ischemic stroke, and 4.9 million cases of ischemic heart disease are caused by hypertension (3).…”
Section: Introductionmentioning
confidence: 99%